2017
DOI: 10.1186/s40663-017-0093-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of canopy-layer composition on understory plant diversity in southern temperate forests

Abstract: Background: Understory plants represents the largest component of biodiversity in most forest ecosystems and plays a key role in forest functioning. Despite their importance, the influence of overstory-layer composition on understory plant diversity is relatively poorly understood within deciduous-evergreen broadleaved mixed forests. The aim of this work was to evaluate how tree overstory-layer composition influences on understory-layer diversity in three forest types (monospecific deciduous Nothofagus pumilio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 41 publications
1
50
1
8
Order By: Relevance
“…Hosting a large number of plant species, fauna, and microflora, understory vegetation was regarded as a forest ecosystem driver in boreal forests [28]. Many studies have found that the diversity (e.g., alpha and beta diversity) and composition of understory plant communities were strongly influenced by canopy composition or forest type [21,29]. In boreal forests, Vaccinium uliginosum, one shrub from family Ericaceae, frequently dominates or is subordinate in understory vegetation [26].…”
Section: Introductionmentioning
confidence: 99%
“…Hosting a large number of plant species, fauna, and microflora, understory vegetation was regarded as a forest ecosystem driver in boreal forests [28]. Many studies have found that the diversity (e.g., alpha and beta diversity) and composition of understory plant communities were strongly influenced by canopy composition or forest type [21,29]. In boreal forests, Vaccinium uliginosum, one shrub from family Ericaceae, frequently dominates or is subordinate in understory vegetation [26].…”
Section: Introductionmentioning
confidence: 99%
“…El conocimiento del ensamble de especies y las propiedades de los diferentes elementos originales del paisaje permiten, además, comprender el potencial multifuncional de los ecosistemas involucrados (O'Farrell y Anderson, 2010;Fischer et al, 2014), pues la producción de servicios ecosistémicos básicos se soporta en la biodiversidad, que fortalece la capacidad de recuperación ante presiones externas (por ej. cambio climático) (Fischer y Lindenmayer, 2007;Martínez Pastur et al, 2017). Figura 1.7.…”
Section: Principios Fundamentales Del Manejo Forestal Sustentableunclassified
“…Por esa razón en este trabajo se aplicó un enfoque a multiescala (Figura 1.11) para proponer estrategias innovadoras de conservación de la biodiversidad en los bosques de Nothofagus de Tierra del Fuego, a los fines de explorar las relaciones entre las semejanzas y diferencias en la composición específica de las comunidades vegetales de fisonomías típicas del paisaje a distintas escalas, resaltando especies comunes y exclusivas de cada ambiente. Dado que las plantas del sotobosque podrían proporcionar indicaciones importantes de conjuntos bióticos de diferentes taxones (Lencinas et al, 2008b;Mestre et al, 2017), en este trabajo se discute la utilidad potencial del enfoque a múltiples escalas a través de plantas vasculares utilizadas como indicadores de biodiversidad en la Isla de Tierra del Fuego. Se espera que este trabajo contribuya con la posible implementación de las acciones propuestas para la conservación de los bosques en el marco de la Ley 26 331.…”
Section: Estrategias De Conservación De La Biodiversidad En Tierra Deunclassified
See 2 more Smart Citations